2022
DOI: 10.1177/02692163221128702
|View full text |Cite
|
Sign up to set email alerts
|

Health and disability care providers’ experiences and perspectives on end-of-life care needs of individuals with long-standing physical disability: A qualitative interview study

Abstract: Background: Little is known about the specific needs and experiences of individuals with long-standing physical disability at end of life. Aim: To explore health and disability care providers perspectives and experiences in relation to end-of-life care needs of individuals with long-standing physical disability. Design: Qualitative study using reflexive thematic analysis. Setting/participants: Semi-structured interviews were conducted with nine health and disability care providers from two Australian states. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A study in the United States revealed that in the last year of life, the incidence of hospice admission among older adults (aged ≥ 70) in a specific month increased by 10% for each additional disability [6]. Interviews have shown that balancing disability support and end-of-life care is difficult even for patients with long-term physical disabilities [7]. Things can only be more challenging when both disability support needs and end-of-life care needs quickly emerge shortly before death.…”
Section: Disability In Older Adults Prior To Deathmentioning
confidence: 99%
“…A study in the United States revealed that in the last year of life, the incidence of hospice admission among older adults (aged ≥ 70) in a specific month increased by 10% for each additional disability [6]. Interviews have shown that balancing disability support and end-of-life care is difficult even for patients with long-term physical disabilities [7]. Things can only be more challenging when both disability support needs and end-of-life care needs quickly emerge shortly before death.…”
Section: Disability In Older Adults Prior To Deathmentioning
confidence: 99%